Characterization of Two TNF-Related Subtypes Predicting Infliximab Therapy Responses in Crohn’s Disease - Ye, Chenglin; Zhu, Sizhe; Yuan, Jingping (Frontiers in Immunology, 2022)
Background: Anti-tumor necrosis factor (TNF) therapy is widely used to treat Crohn’s disease (CD). Unfortunately, 10-40% of patients have primary nonresponse to anti-TNF therapy. TNF family genes play crucial roles in inflammation and immune regulation; however, the effects of TNF family genes on CD remain unclear. Methods: CD expression profiles were downloaded from the Gene Expression Omnibus database. Unsupervised clustering was then used to identify the gene subtypes in CD based on the expressions of TNF family genes. The features of the gene subtypes were characterized using functional enrichment and immune infiltration analyses, and biomarkers of the gene subtypes were identified. Results: CD patients were divided based on unsupervised clustering into two gene subtypes: immune and metabolic. Gene subtype A was significantly correlated with leukocyte migration and cytokine interactions, whereas gene subtype B was associated with metabolic pathways. While 89.5% of the patients in gene subtype B responded to infliximab, only 16.7% of patients in gene subtype A responded. Additionally, a combination of interleukin 1 beta (IL1β), interleukin 6 (IL6) and toll-like receptor 4 (TLR4) can effectively distinguish between gene subtypes A and B. Conclusion: Comprehensive analyses of the TNF family genes may reveal the underlying pathogenesis of CD. The classification of subtypes may provide new ideas for the personalized treatment of patients with CD.